Introspeksi Sifat Munafik Perspektif Hadis - Siti Vania Nuraida; Reza Pahlevi Dalimunthe (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the hadith about the nature of hypocrisy. This study uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about hypocrisy in the history of Bukhari no. 5630. The results and discussion of this study indicate that the status of the hadith is authentic with the qualifications of maqbul ma'mul bih for the practice of Islam to avoid and combat hypocrisy. This study concludes that the hadith narrated by Bukhari no. 5630 is relevant to be used as introspection in maintaining the heart in order to avoid hypocritical traits that endanger personal life and social life.